PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA BENDA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS 4 SD - Desi Indriyani; Fitria Meilina; Tisrin Maulina Dewi; Zulfiana Dessyka Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to improve the science learning outcomes of class 4A students. This research was conducted in October 2022. Researchers applied the discovery learning model to improve student learning outcomes. Learning improvement research was carried out in two cycles. The discovery learning model is a discovery learning model which is a learning method that directs students to learn, explore, discover, and develop their own theories and concepts according to their own abilities but still under the supervision of the teacher. In the pre-cycle, the science learning outcomes of students in class IVA were still low because only 43% of students achieved KKM scores. In the first cycle learning outcomes table, it shows an increase, namely 50% of students can achieve KKM scores. Furthermore, the learning outcomes of cycle II also showed an increase when compared to cycle I. In cycle II, 93.75% of students were able to achieve a completeness score. So, it can be concluded that the discovery learning model assisted by concrete object media can improve students' science learning outcomes. Key words: discovery learning, Concrete Objects, Learning Outcomes